THE ROLE OF CREATIVE ASPECTS IN THE WORK OF FUTURE MUSIC TEACHERS - Utanov Utkir Qurbonovich; Urinova Sabina Shukhrat qizi (Scholar Express Journal, 2022)
The content of creativity, its aspects, common and differences between creativity and creativity parameters, importance of creativity in pedagogical processes are discussed in the article. The value of creativity parameters in the work of future music teachers is discussed.
Keywords: Creativity; technology; parameter; motivation